West Nile Virus Seroprevalence, Connecticut, USA, 2000–2014 - Cahill, Megan E. (Emerg Infect Dis, 2017)
West Nile virus (WNV) infection is mainly asymptomatic but can be severe in elderly persons. As part of studies on immunity and aging in Connecticut, USA, we detected WNV seroconversion in 8.5% of nonimmunosuppressed and 16.8% of immunosuppressed persons. Age was not a significant seroconversion factor. Our findings suggest that immune factors affect seroconversion.